2022
DOI: 10.1017/s1047951122001329
|View full text |Cite
|
Sign up to set email alerts
|

Paediatric cardiologist adherence to American Heart Association neurodevelopmental recommendations for CHD patients

Abstract: A 2012 American Heart Association statement concluded that children with CHD are at an increased risk for neurodevelopmental delays. Routine surveillance and evaluation throughout childhood are recommended. To assess paediatric cardiologist compliance with American Heart Association guidelines and developmental referral practices, a survey was distributed to paediatric cardiologists nationwide (n = 129). The majority of participants (69%) stated they were somewhat familiar or not familiar with the American Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 20 publications
(20 reference statements)
0
7
0
Order By: Relevance
“…Additionally, in one survey of paediatricians and family physicians, 9 only half routinely referred children with CHD for formal developmental evaluation. Similarly, in another survey, 55 only 45% of paediatric cardiologists without access to a developmental follow‐up programme routinely performed neurodevelopmental surveillance. Consequently, authors of these surveys perceived care to be suboptimal, and concluded that many high‐risk children did not seem to be receiving appropriate care to meet their developmental needs.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…Additionally, in one survey of paediatricians and family physicians, 9 only half routinely referred children with CHD for formal developmental evaluation. Similarly, in another survey, 55 only 45% of paediatric cardiologists without access to a developmental follow‐up programme routinely performed neurodevelopmental surveillance. Consequently, authors of these surveys perceived care to be suboptimal, and concluded that many high‐risk children did not seem to be receiving appropriate care to meet their developmental needs.…”
Section: Resultsmentioning
confidence: 97%
“…Full‐text screening of these 193 publications resulted in 35 publications being included in this review. 9 , 13 , 14 , 15 , 16 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 The stages of the search and screening process and reasons for exclusion are presented in the PRISMA‐ScR flow diagram (Figure S1 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations